Uses of Periphrastic Do in English - Eltaif, Suaad Abdul- Rahman (Journal of Tikrit University for Humanities, 2022)
This study aims at clarifying the definitions, structures ,conditions and uses of Periphrastic Do (PD) in English. PD is an auxiliary , it is an alternative device for using inflection process. It is semantically not intrinsic but syntactically obligatory. It is used to satisfy the needs of the sentence structures. It can be used in verbal negation, negative preposed constituents, inverted questions, anphoric PD and tag questions. In these structures , only the use of PD is correct and necessary . It is a syntactic device that performs a special function. During the years, PD underwent a change and development from zero to obligatory use in specific contexts.